Nurses’ Knowledge Regarding Laparoscopic Cholecystectomy: Pengetahuan Perawat Mengenai Kolesistektomi Laparoskopi - Al-Tameemi , Adil Atiyah Mohammed (Academia Open, 2024)
Background: The most effective treatment for gallstones is laparoscopic cholecystectomy due to the many benefits of open surgery, including fewer incisions, shorter hospital stays, the elimination of the need for a stomach tube and drainage tube, fewer analgesics, and fewer problems. Objectives: To identify nurses’ knowledge regarding laparoscopic cholecystectomy. Methods: A descriptive investigation was conducted between September 15, 2022, and July 20, 2023. The Al-Sader Teaching Hospital and the Basrah Teaching Hospital in Basrah City are the sites of the investigation. A deliberate non-probability sample of surgical ward nurses was chosen. Two hundred nurses make up the sample. A panel of specialists assessed the questionnaire’s validity, and a pilot study proved its dependability. Data was gathered using the questionnaire, and the findings were analyzed using both descriptive and inferential statistics. Results: According to the table’s findings, the majority of nurses (76%) have little understanding of cholecystectomy, 20% have medium knowledge, and 4% have strong knowledge, with a mean score and standard level deviation of 1.59+0.709. Conclusion: This study concluded, most of the study sample have low knowledge about cholecystectomy. Highlights: Laparoscopic cholecystectomy offers advantages over open surgery Assess nurses’ knowledge on laparoscopic cholecystectomy Most nurses have low knowledge about cholecystectomy. Keywords: Nurses, Knowledge, Laparoscopic, Cholecystectomy